스트레스와 인지장애 - 김수정(Soo-Jeong KIm); 변광호(Kwang-Ho Pyun); 심인섭(Insop Shim) (Seuteureseu yeon-gu (Online), 2005)
Prolonged and repeated stress can lead to excessive glucocorticoid (GC) secretion that is accomplished by the hypothalamo- pituitary-adrenocortical (HPA) axis and can constitute a serious risk for the organism. A hypersecretion of GCs was associated with neuropsychiatric changes including anxiety and affective disorders as well as a variety of neurobiological changes including neuroendocrine disturbances, cortical atrophy and hippocampal degeneration. Several of these changes have been associated with cognitive impairment. In recent literature, the central action of GCs has mostly been portrayed as damaging and disruptive to memory formation. In this paper, we describe the effects of stress on learning and memory, and review potential cellular and neural mechanisms underlying the effects of stress on cognitive dysfunction in terms of roles of GC and structural changes of the hippocampus by chronic stress. (Korean J Str Res 2005;13:283～288) Prolonged and repeated stress can lead to excessive glucocorticoid (GC) secretion that is accomplished by the hypothalamo- pituitary-adrenocortical (HPA) axis and can constitute a serious risk for the organism. A hypersecretion of GCs was associated with neuropsychiatric changes including anxiety and affective disorders as well as a variety of neurobiological changes including neuroendocrine disturbances, cortical atrophy and hippocampal degeneration. Several of these changes have been associated with cognitive impairment. In recent literature, the central action of GCs has mostly been portrayed as damaging and disruptive to memory formation. In this paper, we describe the effects of stress on learning and memory, and review potential cellular and neural mechanisms underlying the effects of stress on cognitive dysfunction in terms of roles of GC and structural changes of the hippocampus by chronic stress. (Korean J Str Res 2005;13:283～288) KCI Citation Count: 1